Does Size Matter for IPO Survival? Empirical Evidence from India. Issue 1 (March 2018) - Baluja, Garima
This article examines the effect of size of new issues on their survival profile in the aftermarket. The relationship between the probability of delisting and the time duration of initial public offerings (IPOs) on Bombay Stock Exchange (BSE) is tested using logistic regression and parametric survival analysis models. The models take a range of information concerning offering, market and corporate specific characteristics as well to explore the outcome of IPOs on the trading exchange. The analysis of Kaplan–Meier curves provides insight about how size matters in determining the survival and hazard trend of IPO in the aftermarket. Overall, the study reveals that issues with large size exhibits more market confidence as well as ability to withstand the rough market situations in the aftermarket, and hence, they survive longer in the market. The analysis of other variables shows a positive influence of age, lead manager's reputation and IPO demand, whereas negative influence of risk, list delay, underpricing, market level and IPO activity on the survival probability as well as duration of IPOs in the aftermarket. Further, the survival prospects are analysed across several industrial sectors as well. The present study provides useful insight to several parties associated with IPOs, such as investors, issuers, creditors and regulators, who can utilize this information for taking rational decisions.